Creation of Database of Protocols for Dispensing and Preparation of Cancer Drugs and its Application - Kumai, Masayoshi; Mabuchi, Tomomi; Takekuma, Yoh; Miyamoto, Takenori; Fujiwara, Toshie; Iwai, Miwako; Sugawara, Mitsuru; Suda, Noriyuki; Ogino, Osamu; Miyazaki, Katsumi; Kawagishi, Toru; Matsuura, Maya (Iryo Yakugaku (Japanese Journal of Pharmaceutical Health Care and Sciences), 2005)
The results of cancer chemotherapy have been improved remarkably by the development of new drugs and combining drugs in treatment. However, cancer chemotherapy protocols are complicated and the adverse effects are more severe than those of other pharmacotherapies. It was therefore felt important to create a database of protocols for the preparation and dispensing of drugs used in cancer chemotherapy. Using Microsoft Access, we have created a database from 320 protocols we have collected so far from 12 clinical departments and developed operating programs for it. The database has enabled us to search for a protocol using keywords-names of drugs, diseases and clinical departments-and most of the operations can be carried out by the click of a mouse. With our database, pharmacists are able to access protocols quickly and check prescriptions of anticancer drugs even if they are unfamiliar with computers, and we consider it to be a useful tool for this purpose.